Grammatical Error Analysis in EFL Students’ Recount Text Writing - Hasan, Hasan; Sadapotto, Andi; Usman M, Usman M; Hanafi, Muhammad (Majesty Journal, 2023)
Writing recount texts requires students to retell past experiences coherently while applying appropriate grammatical features, especially past tense forms, prepositions, noun pluralization, articles, pronouns, conjunctions, and punctuation. However, EFL students frequently experience difficulties in producing grammatically accurate recount texts. This study aims to identify and classify the most frequent grammatical errors found in students’ recount text writing. The study employed a descriptive quantitative design involving 40 third-year students selected through purposive sampling. Data were collected from students’ written recount texts about unforgettable personal experiences, which were written in class within 60 minutes. The data were analyzed using an error analysis procedure consisting of error identification, classification, tabulation, and percentage calculation. The errors were categorized into verb forms, prepositions, noun pluralization, articles, pronouns, conjunctions, and punctuation or writing mechanics. The findings revealed that verb form errors were the most frequent, occurring in 92.5% of students’ texts, followed by preposition errors at 85%, noun pluralization errors at 75%, article errors at 57.5%, pronoun errors at 52.5%, conjunction errors at 37.5%, and punctuation errors at 22.5%. These results indicate that students had not fully mastered the grammatical features required in recount writing, particularly the consistent use of past tense forms. The study suggests that grammar instruction should be integrated with genre-based writing practice, explicit feedback, and remedial activities focused on students’ recurring grammatical problems. The findings provide pedagogical input for English teachers in designing more effective writing instruction to improve students’ grammatical accuracy and overall writing quality.